THU0040 PROTEINASE 3-REACTIVE B CELL RECONSTITUTION AFTER TREATMENT WITH RITUXIMAB FOR ANCA-ASSOCIATED VASCULITIS. (2nd June 2020) - Berti, A.; Hillion, S.; Hummel, A.; Carmona, E.; Peikert, T.; Langford, C.; Merkel, P. A.; Monach, P.; Seo, P.; Spiera, R.; St Clair, E. W.; Fervenza, F.; et al.
Abstract : Background: Proteinase 3 (PR3)-reactive B cells are present in PR3-ANCA-associated vasculitis (AAV) at levels higher than healthy controls. Objectives: To evaluate the dynamics of the PR3-reactive B cell repopulation in patients with PR3-AAV after treatment with rituximab, and to analyze possible associations between these immunological changes and long-lasting remissions. Methods: We analyzed all available frozen peripheral blood mononuclear cells (n=148) from 23 randomly-selected PR3-AAV patients who participated in the RAVE trial and achieved complete remission (BVAS=0, prednisone=0) after treatment with rituximab. We measured PR3-reactive B cells and the relative subsets by a multi-color flow cytometry panel including CD19, IgD, CD27, CD38, CD24, and a biotinylated PR3 revealed by fluorescent streptavidin. The clinical data of the trial were correlated with flow-cytometry data. Results: 10/23 (43%) patients relapsed during the follow up, 8/10 relapses were severe. At baseline, clinical features, PR3-ANCA levels, % of total PR3-reactive B cells and PR3-reactive B cell subsets were similar between relapsers and non-relapsers. All patients were followed until the end of the trial, for a mean of 44 months (25-75%IQR 31-54), without difference in follow-up time between relapsers and non-relapsers (p=0.98). The majority of patients had B cell repopulation at 12 (range 12-24) months after rituximab. At the time of B cell repopulation, transitional (CD19+CD24+CD38+) and naïve (CD19+CD27+IgD-) B cells were higher compared to baseline, while total plasmablasts (PB) were unchanged, and mature B cells significantly decreased in both relapsers and non relapsers. PR3-reactive B cells reappeared in all the patients, and the % of PR3-reactive of B cells were higher at the B cell repopulation visit compared to baseline (5.82% vs 4.25%, p<0.05), while total B cells were lower (66/μL vs 151/μL, p<0.01), regardless of future relapse. Within PR3-reactive B cells, only the % of PB (CD19+CD27+CD38+PR3+) were higher in relapsers vs. non-relapsers (median [25-75%IQR]; 1.95% [1.315-3.845] vs 0.84% [0.05-1.66], p=0.022) and severe relapsers vs non-severe relapsers (2.165% [1.66-4.315] vs 0.84% [0.1-1.74], p=0.015). Time-to-relapse and time-to severe-relapse were significantly shorter in patients with circulating PR3-PB higher than the median value of the cohort (1.6%) during B cell reconstitution (Figure 1A -B). Conclusion: In PR3-AAV, during B cell reconstitution after rituximab, the total fraction of PR3-B cells increases, due to the expansion of the transitional and naïve B cell compartments. Circulating PR3-PB within PR3-B cells are enriched in the peripheral blood of relapsing and severely relapsing patients compared to non-relapsing patients. Higher levels of PR3-PB after rituximab during B cell reappearance significantly increased the risk of subsequent relapse and severe relapse. References: [1]Cornec D, Berti A, Hummel A, et al. J Autoimmun. 2017 Disclosure of Interests: Alvise Berti: None declared, Sophie Hillion: None declared, Amber Hummel: None declared, Eva Carmona: None declared, Tobias Peikert: None declared, Carol Langford: None declared, Peter A. Merkel: None declared, Paul Monach: None declared, Philip Seo: None declared, Robert Spiera Grant/research support from: Roche-Genetech, GSK, Boehringer Ingelheim, Chemocentryx, Corbus, Forbius, Sanofi, Inflarx, Consultant of: Roche-Genetech, GSK, CSL Behring, Sanofi, Janssen, Chemocentryx, Forbius, Mistubishi Tanabe, E. William St. Clair: None declared, Fernando Fervenza: None declared, Kristina Harris: None declared, John H. Stone Grant/research support from: Roche, Consultant of: Roche, Jacques-Olivier Pers: None declared, Ulrich Specks: None declared, Divi Cornec: None declared